2013
DOI: 10.1097/aln.0b013e318291079c
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of the AMPAKINE CX717 with Propofol Reduces Respiratory Depression and Fatal Apneas

Abstract: Background: Propofol (2,6-diisopropylphenol) is used for the induction and maintenance of anesthesia in human and veterinary medicine. Propofol's disadvantages include the induction of respiratory depression and apnea. Here, the authors report a clinically feasible pharmacological solution for reducing propofol-induced respiratory depression via a mechanism that does not interfere with anesthesia. Specifically, they test the hypothesis that the AMPAKINE CX717, which has been proven metabolically stable and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
(39 reference statements)
1
24
0
Order By: Relevance
“…20,21 By increasing excitatory inputs in neurons of the pre-Botzinger complex in the medulla, AMPAkines can stimulate the respiratory drive 26,27,71-73 to treat or prevent hypoventilation caused by sedatives often used intra- or postoperatively. 26,28,74,75 A previous study has shown the effect of AMPAkines in persistent or chronic pain. Our current study demonstrates that these drugs can also effectively relieve the incisional pain commonly associated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 By increasing excitatory inputs in neurons of the pre-Botzinger complex in the medulla, AMPAkines can stimulate the respiratory drive 26,27,71-73 to treat or prevent hypoventilation caused by sedatives often used intra- or postoperatively. 26,28,74,75 A previous study has shown the effect of AMPAkines in persistent or chronic pain. Our current study demonstrates that these drugs can also effectively relieve the incisional pain commonly associated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 By increasing AMPA receptor-mediated currents in neurons of the pre-Botzinger complex in the medulla, AMPAkines directly stimulate the respiratory drive, 26,27,4749 and they have been shown to treat or prevent hypoventilation caused by opioids and propofol. 26,28,50,51 The effect of AMPAkines in chronic pain, however, has not been previously studied. The analgesic dose for CX546 found in our study is comparable to the dose tested in rats to treat respiratory depression.…”
Section: Discussionmentioning
confidence: 99%
“…CX717 has been used in both animal models (15,17,20) and clinical trials to alleviate respiratory depression due to opioids (14). CX717 does not directly antagonize opioid receptors, because, in both rats and humans, CX717 counteracts respiratory depression without influencing analgesia (15)(16)(17)20). Animal studies have confirmed that CX717 stimulates breathing by potentiating AMPA currents in respiratory neurons, including both motor and premotor neurons (15,20).…”
Section: Ampakines and Their Use In Treating Hypoventilationmentioning
confidence: 91%
“…These drugs successfully stimulated breathing after opiate-induced respiratory depression in clinical trials (13,14). Importantly, preclinical studies show that ampakines most effectively stimulate breathing when the neural input to respiratory muscles is blunted (13,(15)(16)(17). Ampakines may therefore be a therapeutic option for respiratory insufficiency, particularly when neuromotor impairment is suspected.…”
mentioning
confidence: 99%